-15v+9=-20v-9

Simple and best practice solution for -15v+9=-20v-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15v+9=-20v-9 equation:


Simplifying
-15v + 9 = -20v + -9

Reorder the terms:
9 + -15v = -20v + -9

Reorder the terms:
9 + -15v = -9 + -20v

Solving
9 + -15v = -9 + -20v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '20v' to each side of the equation.
9 + -15v + 20v = -9 + -20v + 20v

Combine like terms: -15v + 20v = 5v
9 + 5v = -9 + -20v + 20v

Combine like terms: -20v + 20v = 0
9 + 5v = -9 + 0
9 + 5v = -9

Add '-9' to each side of the equation.
9 + -9 + 5v = -9 + -9

Combine like terms: 9 + -9 = 0
0 + 5v = -9 + -9
5v = -9 + -9

Combine like terms: -9 + -9 = -18
5v = -18

Divide each side by '5'.
v = -3.6

Simplifying
v = -3.6

See similar equations:

| 10p-45=3(b-15) | | 58454+n=58454 | | 7g+9=44 | | (x)(4x)=192 | | 3x-21+5x=16+6x-11 | | 2a-3b+1=0 | | 3f-27=-3 | | 3y-6=18-y | | 4x-2x(4+6)=-22 | | 4.9t^2+4t-50=0 | | 8e+5=21 | | 6(z-4)=12 | | 4x+9y+3(x+y)= | | 2/3x+4=7/3x-12 | | 3d+7=-11 | | 72=8(s-2) | | 2x=7x+5 | | 72=8(-2) | | 2k+21=35 | | 4secx+9=0 | | 6(5-8x)+12=-5x | | (2a-3b+1)=0 | | 5(v+1)=7v-15 | | -6.9(4t+6)-2.9(3t-5)= | | 12x=2(x+10) | | 5t-3t-14=0 | | 3x-4=2(2x+6) | | 2c-5=15 | | 44+20=h | | P+p+o=4 | | 12-s=14 | | 98=-3(-2x-7)+5x |

Equations solver categories